FREQUENCY OF HEPATITIS-B AND C IN PATIENTS ON HAEMODIALYSIS FOR END STAGE RENAL DISEASE IN TERTIARY CARE HOSPITALS: A MULTICENTRE STUDY - Asif, Muhammad; Ahmed, Raheel; Ahmed, Tanveer; Uddin, Zia; Zahid, Muhammad; Ullah, Izzat (Journal of Ayub Medical College Abbottabad, 2020)
Background: Patients undergoing haemodialysis are at increased risk for acquiring infections like hepatitis B virus and hepatitis C virus. This is due to their underlying impaired cellular immunity and exposure to contaminated equipment, frequent blood transfusions, hospitalization and surgery. This study was conducted to determine the frequency of Hepatitis B and C in patients undergoing haemodialysis in tertiary care hospitals. Methods: This cross-sectional study was conducted in dialysis units of three tertiary care hospitals, from January to August 2018. Data regarding demographics and hepatitis status was collected from patients and hospital records through a structured questionnaire. Categorical variables were shown in percentages and Chi square test was used to see association between hepatitis status and age, gender and duration of dialysis. Results: Of the total 521 patients, 318 (61%) were males. Mean age of participants was 44.98±16.51 years and mean duration since initiation of HD 19.74 months. Of the total, 150 (28.8%) were hepatitis C positive, 28 (5.4%) were hepatitis B positive and 18 (3.4%) having hepatitis B and C co-infection. Duration since initiation of dialysis was associated with hepatitis (p<0.001). Percentage of hepatitis was higher in males compared to females but statistically not significant. Conclusion: The frequency of hepatitis in our haemodialysis units is alarmingly high and significantly associated with duration since initiation of haemodialysis. Keywords: ESRD; Haemodialysis; Hepatitis C; Hepatitis B and Prevalence